The Measurement of Sustainable Development in Indonesia - Fauzi, Akhmad; Oxtavianus, Alex (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
Nearly the end of the Millennium Development Goals (MDGs) era, bring back ideas for looking international development goals. Sustainable Development Goals (SDGs) is one of them. In this study, sustainable development has defined as the balance of economic, social and environmental. The achievement of sustainable development is measured by using two different approaches, partial and composite indicator. Partial development indicators showed progress in economic and social dimensions. However, progress in these areas seems to put pressure on the environment. Sustainable Development Index (IPB), which is a composite of GDP, HDI and IKLH (Environmental Quality Index) also gives the same message. By using a balance between dimensions of development technique, as chosen scenario, sustainable development in Indonesia reached about two-thirds of the maximum target. Hight progress in economic and social ultimately corrected by environmental degradation.